The Use of Quizizz Online Assessment Tools for Chemistry Learning During Limited Face-to-Face Learning - Hasibuan, Desy Rahmayanti; Daulay, Rabiah Afifah; Nasution, Annisa (LAVOISIER: Chemistry Education Journal, 2022)
This study aims to determine the use of Quizizz online assessment media in chemistry learning during limited face-to-face learning (PTMT). During the PTMT period, many applications were used for assessment, one of which was Quizizz. Quiziz online assessment media with its various advantages has assisted educators in conducting online learning assessments, so that difficulties in assessment during the PTMT period can be overcome. This study uses a descriptive approach with quantitative and qualitative methods. Respondents were 45 students of 11th grade of Insan Cendikian Islamic High School in South Tapanuli, North Sumatera, Indonesia. This study implemented in the odd semester of the 2020/2021 school year. The results of the questionnaire given to the students it was concluded that the use of Quizizz media in assessment in chemistry learning could overcome problems in assessment during the PTMT period. This Quizizz online assessment method has bridged distance and time in chemistry learning which motivates students.